Pemanfaatan Asam Laktat Hasil Fermentasi Limbah Kubis Sebagai Pengawet Anggur Dan Stroberi - ALIYA, HIMAA; MASLAKAH, NISAUL; NUMRAPI, TIWI; BUANA, AJENG PUSPA; HASRI, YOLA NOVITA (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
Mountain Magelang is one of agricultural sectors that produces cabbage, which will then be delivered to market Ngablak, Magelang. The unsold cabbage usually becomes waste which can damage the environment, but at the other side, it can become food preservative if it is fermentated. The objective of this research is to utilize the lacted acid from the fermentation of cabbage waste as the preservative of strawberries and grapes. This research is an experiment research, whose steps include: fermentation of cabbage waste with NaCl as much as 3%, microbiology and organoleptic test. The organoleptic test includes flavour, texture and color. The sample of this cabbage waste is obtained from market Ngablak Magelang Regency, while the strawberry and grape sample is then obtained from Cemoro Sewu, Sarangan area. As much as 20 strawberries and grapes are used in this research, which is divided into 2 groups. These groups are control group and treatment group with the total of fruits for each group as much as 10 fruits. For the treatment group, each 10 fruits (grapes and strawberries) are submerged in 100ml of the lactid acid solution from the fermentation of cabbage waste as long as 1 to 7 times 24 hours. The result of microbiologic test shows that the amount of microbes in grapes on the day-1 control is as much as 2.1 times 10-4 col/grams. At the treatment is as much as 3.3 times 10-5 col/grams, while on the control day-5, the amount of microbes are as much as 3.6 times 10-6 col/grams and on the treatment day-5 is as much as 6.0 times 10-6 col/grams. The amount of microbes in strawberries on the control day-2 are as much as 5.0 times 10-5 col/grams and is as much as 7.1 times 10-5 col/grams for the treatment day-2. While on the control day-5, the amount of microbes are as much as 3.0 times 10-6 col/grams and are as much as 5.8 times 10-6 col/grams for the treatment day-5. For the result of organoleptic test of grapes on the control day-1, the fruits’ colour are semi brown, the flavour is (+++). The fruit reduced around 0.406 grams and expandes as much as 0.22 grams for the treatment day-1. Meanwhile on the control day-5, the fruits’ color are blackish red, with (+++) flavour and the fruits did not shrink. On the treatment day-5, fruits’ color are still fresh-red with (+) flavour and the fruits’ size increase as much as 1.398 grams.The result of organoleptic test of strawberries show that the color of the fruits on the control day-1 are brownish red with (+++) flavour. The fruits shrink as much as 2.479 grams. On the treatment day-1, they shrink as much as 0.901 grams, meanwhile on the control day-5 the fruits’ color are blackish red with (++) flavour. The fruits shrink as much as 10 grams. On the treatment day-5, the fruits’ color are faded red with (+) flavour. The fruits’ size increase as much as 2.172 grams. The conclusion is that the amount of microbes in the treatment group is more than the amount of microbes in the control group because of the lactid acid bacteria, and the shrink in the control group is bigger than in treatment group. Finally, it can be concluded that the lactid acid from cabbage waste fermentation can be utilized as the preservative of strawberries and grapes.